Taking the Next Step in Using Technology - Trinidad, Sue (Pearson Education Asia, 2005)
FOCUS: Take a moment to think about how you or your colleagues use technology in the classroom or teaching environment. What can be done differently with technology? How might you or your colleagues move to the next step? How might you take a leadership role in this change?Using ICT in education is about people and helping people understand what good learning is and how building effective learning environments can be supported by ICT. This book describes policies, projects, models and case studies that have been used in different regions to encourage and maintain the use of ICT in education change, leadership and best practice.